2017
DOI: 10.1099/mgen.0.000104
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the Streptococcus mutans transcriptome by LrgAB and environmental stressors

Abstract: The Streptococcus mutans Cid/Lrg system is central to the physiology of this cariogenic organism, affecting oxidative stress resistance, biofilm formation and competence. Previous transcriptome analyses of lytS (responsible for the regulation of lrgAB expression) and cidB mutants have revealed pleiotropic effects on carbohydrate metabolism and stress resistance genes. In this study, it was found that an lrgAB mutant, previously shown to have diminished aerobic and oxidative stress growth, was also much more gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(50 citation statements)
references
References 68 publications
3
47
0
Order By: Relevance
“…In addition, it has been shown that a ΔlrgAB mutant presented transcriptomic profile distinct from the ΔlytS mutant, even though LytST controls expression of lrgAB, 29 suggesting that changes in gene expression by the mutation of lrgAB could be independent of LytST. 55 As pointed out earlier, it is possible that changes on the cell membrane could explain some of the distinct and even unexpected expression patterns, and hence, future research on membrane composition and structure deserves attention.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, it has been shown that a ΔlrgAB mutant presented transcriptomic profile distinct from the ΔlytS mutant, even though LytST controls expression of lrgAB, 29 suggesting that changes in gene expression by the mutation of lrgAB could be independent of LytST. 55 As pointed out earlier, it is possible that changes on the cell membrane could explain some of the distinct and even unexpected expression patterns, and hence, future research on membrane composition and structure deserves attention.…”
Section: Discussionmentioning
confidence: 96%
“…To measure growth-dependent expression of genes related to pyruvate metabolism, cells were harvested in early-exponential and -stationary growth phases. Extraction of RNA, qPCR, and data analysis were performed as described elsewhere Ahn and Rice, 2016;Rice et al, 2017). Expression was normalized against an internal standard (gyrA).…”
Section: Quantitative Real-time Pcr (Qpcr) Assaymentioning
confidence: 99%
“…Furthermore, as the ΔgtfB biofilm aged, the expression of lytS decreased, being inversely proportional to the increase of expression recorded for lrgAB, which was not observed for UA159 biofilms. Even though LytST controls the expression of lrgAB, a ΔlrgAB mutant presented a distinct transcriptomic profile from the ΔlytS mutant [45], suggesting that changes in gene expression by the mutation of lrgAB could be independent of LytST [59]. Further comparison of transcriptomics and proteomics of a ΔlrgAB mutant (vs. the parental strain) subjected to distinct oxidative, heat and antimicrobial stresses indicated 'that adaptation to a new environment may require radical proteome turnover or metabolic remodeling' [50].…”
Section: Discussionmentioning
confidence: 98%